Development of Video Tutorials as a Guide to Guided Inquiry-Based Practicum on Senior High School Biology Material - Mariani Natalina; Hikmah Hidayah; Darmadi (Postgraduate, University of Mataram, 2024)
This study aims to produce guided inquiry-based video tutorials as practicum instructions on quality plant tissue structure and function material. The type of research conducted is Research and Development (R&D) using the ADDIE model (Analyze, Design, Development, Implementation and Evaluation) which is limited to the third stage. The instruments used in this study were validation sheets and response questionnaires. This research was conducted at SMAN 8 Pekanbaru. The assessment was carried out in the form of filling out validation sheets by two experts, namely a media expert and a biology material expert as well as two senior high school biology teachers. The video tutorial validation results obtained an average score of 3.66 with a very valid category. The video tutorial was tested on eighth semester biology education students in the limited trial phase I with a score of 3.69 with a very good category. Then the video tutorial was tested in a limited trial phase II with grade XI students with a score of 3.69 with a very good category. Based on the average score obtained from the validation and trial results, it can be concluded that the guided inquiry-based practicum video tutorial has very good quality with a score of 3.68.